Not just words! Effects of a light-touch randomized encouragement intervention on students' exam grades, self-efficacy, motivation, and test anxiety - Tamás Keller; Péter Szakál (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
Motivated by the self-determination theory of psychology, we ask how simple school practices can forge students' engagement with the academic aspect of school life. We carried out a large-scale preregistered randomized field experiment with a crossover design, involving all the students of the University of Szeged in Hungary. Our intervention consisted of an automated encouragement message that praised students' past achievements and signaled trust in their success. The treated students received encouragement messages before their exam via two channels: e-mail and SMS message. Control students did not receive any encouragement. Our primary analysis compared the end-of-semester exam grades of the treated and control students, obtained from the university's registry. Our secondary analysis explored the difference between the treated and control students' self-efficacy, motivation, and test anxiety, obtained from an online survey before students' exams. In the whole sample, we did not find an average treatment effect on students' exam grades. However, in the subsample of those who answered the endline survey, the treated students reported higher self-efficacy than the control students. The treatment affected students' motivation before their first exam - but not before their second -and did not affect students' test anxiety. Our results indicate that automated encouragement messages sent shortly before exams do not boost students' exam grades. Nevertheless, since occasionally received light-touch encouragement messages instantly increased students' self-efficacy even before an academically challenging exam situation, we conclude that encouraging students systematically and not just shortly before their exams might lead to positive emotional involvement and help create a school climate that engages students with the academic aspect of school life.
Keywords: I23; I21; C93; D91; 330; Preregistered randomized field experiment; encouragement message; exam grades; test anxiety; self-efficacy; motivation